Intake of Vitamin E and C in Women of Reproductive Age: Results from the Latin American Study of Nutrition and Health (ELANS) - Busso, Dolores (2021)
Vitamin E was identified as a lipophilic compound essential to maintain rat pregnancy. Low vitamin E intake during early pregnancy associates with congenital malformations and embryonic loss in animals and with miscarriage and intrauterine growth restriction in humans. Vitamin E protects cell membranes from lipoperoxidation and exerts non-antioxidant activities. Its function can be restored by vitamin C; thus, intake and circulating levels of both micronutrients are frequently analyzed together. Although substantial vitamin E inadequacy was reported worldwide, its consumption in Latin America (LatAm) is mostly unknown. Using data from the Latin American Study of Nutrition and Health (Estudio Latinoamericano de Nutrición y Salud, ELANS), we evaluated vitamin E and C intake in women of reproductive age (WRA) from eight LatAm countries and identified their main food sources. Two non-consecutive 24-h dietary recalls in 3704 women aged from 15 to 49 years and living in urban locations showed low average intake of vitamin E (7.9 mg/day vs. estimated average requirement (EAR) of 12 mg/day) and adequate overall vitamin C consumption (95.5 mg/day vs. EAR of 60 mg/day). The mean regional inadequacy was 89.6% for vitamin E and 36.3% for vitamin C. The primary food sources of vitamin E were fats and oils, as well as vegetables. Vitamin C intake was explained mainly by the consumption of fruit juices, fruits, and vegetables. Combined deficient intake of both vitamins was observed in 33.7% of LatAm women. Although the implications of low antioxidant vitamins' consumption in WRA are still unclear, the combined deficient intake of both vitamins observed in one-third of ELANS participants underscores the need for further research on this topic.